Micro-structural study of colored porcelains of Changsha kiln using imaging and spectroscopic techniques. Issue 15 (15th October 2018) - Shen, Bailin; Sciau, Philippe; Wang, Tian; Brunet, Magali; Li, Jianmao; Lu, Wen; Zhu, Tiequan
Abstract: Changsha kiln was an ancient factory from the Tang Dynasty (618–907 CE) to the Five Dynasties (907–960 CE), famous for its colored porcelain production. It was one of the pioneer sites to master the poly-color technique at high temperature. In this work, by using Energy Dispersive X-Ray Fluorescence (EDXRF), Raman spectroscopy and Scanning Electron Microscopy Energy Dispersive X-ray Spectrometer (SEM-EDS), the composition and structure of two of its emblematic colored glazes were studied. The results confirmed that the chromogenic elements of brown and green colored glazes are well iron and copper respectively. They also revealed a significant presence of hematite (α-Fe2 O3 ) phase with dendritic shape close to the glaze surface and oddly a substantial amount of ε-Fe2 O3 phase at the body/glaze interface. It is the second type of ancient Chinese glaze in which the very rare and metastable iron(III) oxide polymorph was found. No Cu-based particle was identified in green glaze. The green color is certainly due to Cu 2+ dispersed in the glassy matrix. Our study confirmed that Cassiterite (SnO2 ) was used as opacifier compound to obtain opaque green color.